Wpływ funduszy europejskich na innowacyjność lubuskiej gospodarki = The influence of European funds on the innovativeness of the Lubuskie economy - Sługocki, Waldemar (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the impact of the use of EU funds on the process of building innovativeness of the Lubuskie economy in the context of achieving the following objectives: National Strategic Reference Framework (NSRF) 2007 - 2013 and the government strategy named - Strategy for increasing the innovativeness of the economy for the years 2007-2013.
Keywords: fundusze UE; fundusze unijne; województwo lubuskie; innowacyjność; rozwój regionalny